Upaya Merealisasikan Good Governance melalui Pelayanan Publik di Indonesia - Faizul Abror; Defamifta Khuljana (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
In the implementation of public services in Indonesia, it is considered ineffective because there are still many problem phenomena that often arise in its application, for example problems regarding convoluted service procedures, lack of uncertainty given to the community, and high costs. The method used is descriptive qualitative research which explains the realization of good governance, public services, and efforts to improve the quality of public services in Indonesia. the results of this study indicate that the implementation of good governance is still not going well so that the role of the government, the community, and the private sector is needed in implementing improvements to the quality of public services in order to realize good governance. , namely transparency, conducting supervision to avoid various forms of irregularities that occur in the implementation of public services, increasing the role and participation of the community in public services.